Lycée Essay (2): The Truth, when Known / Though Sad, Has yet its Charms - Gramsci, Antonio (International Gramsci Journal, 2024)
The subject of the essay, here in its English version, is taken from Giacomo Leopardi’s poem to Count Carlo Pepoli (Canti, 1841) and reads in English, “… the truth, when known, / Though sad, has yet its charms”. One type of person accepts the world as it is, seeing only its beautiful side, is transported by dreams and refuses to take into account cruel truths. Others detach themselves from the human herd, not being content with vain appearances; they are driven by the desire to know but risk becoming total sceptics. A third type looks at the world as it is, knowing that the truth they see may be hard to accept, but reason rather than an attack on spurious targets must be used to find it. The real heroism of the “man of thought” is a knowledge of the world as it really is, which entails not hiding unpleasant sides from outsiders, which would amount to a hypocritical “Jesuitism”. Wrong and harmful positions must be attacked, as for example in Emile Zola’s “J’accuse” letter and, in Italy, Giosuè Carducci’s diatribes against the “patriots” who were ruining the young Italian State.